Bourbon Barrels and Bottlenecks: a Nuanced Look at Thirty Years of White Oak Population Dynamics - Lance A. Vickers; Benjamin O. Knapp; Thomas Goff; Thomas J. Brandeis; John M. Lhotka; Randall S. Morin; Kenton L. Sena; Jeffrey W. Stringer (Journal of Forestry, 2025)

A Middle and Late Devensian sequence from the northern part of Kents Cavern (Devon, UK) - Rob Dinnis; John Boulton; Barry Chandler; Jesse Davies; Jennifer C. French; Thomas Higham; Louisa Jáuregui; Mark Lewis; Matthias Meyer; Danielle Schreve; Chris Stringer; Chris Proctor (Journal of Quaternary Science, 2025)
1920s/30s excavation of a Middle Devensian sequence in the northern part of Kents Cavern recovered important Late Middle and Early Upper Palaeolithic archaeological material, including Britain's oldest known Homo sapiens remains. Questions remain about this material, including how it came to be in the cave. Judged by the recorded distribution of finds it may have entered via the Northeast Gallery. A previously unrecorded entrance into the cave from the Northeast Gallery was identified in 2014, and a column through the entrance's sedimentary fill was excavated during 2015–2016. The results of that work are reported here. The entrance retains an intact and well‐stratified Pleistocene sequence comparable to the ‘Cave Earth’ unit described previously inside the cave. The uppermost part of the newly recognised Northeast Gallery entrance sequence has been removed by historical excavation, with most of the remaining sediments spanning the Middle Devensian and earlier part of the Late Devensian. The sequence contains bone and pollen, and ancient mammalian DNA is preserved within the sediments. The base of the Northeast Gallery entrance sequence is formed of a clayey diamict comparable to the cave's ‘Breccia’ unit, a deposit currently understood as Middle Pleistocene, and previously identified only in Kents Cavern's southern chambers. Comparison of the excavated sequence with the historical record of the Vestibule excavation shows that the basal cave earth deposits in the Northeast Gallery entrance are significantly higher than those inside the cave. Although requiring further work to confirm, this suggests that the Northeast Gallery could have played a major role in the accumulation of material in the Vestibule during the Middle Devensian.

Recent advances in sustainable degradation processes of elastomers: a comprehensive review - Manuel Burelo; Itzel Gaytán; Selena Gutiérrez; Jorge A. Cruz-Morales; Cecilia D. Treviño-Quintanilla; Thomas Stringer; Monserrat Ramírez-Melgarejo (Reviews in Environmental Science and Bio/Technology, 2025)

Gender-specific impacts of road accessibility on rural development - Thomas Stringer; Esteban Ricardo García Clavel; Manuel Burelo (Journal of Transport Geography, 2025)

How ecosystem services are co-produced: a critical review identifying multiple research framings - A.J. Woodhead; J.O. Kenter; C.D. Thomas; L.C. Stringer (Ecosystem Services, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Subnational perspectives on energy transition pathways for Mexico's electricity grid - Esteban Ricardo García Clavel; Thomas Stringer; Julio C. Sacramento Rivero; Manuel Burelo (Utilities Policy, 2024)

Physical, Chemical and Compaction Characteristics of Slightly Weathered Tephras of New Zealand - Shaurya Sood; Gabriele Chiaro; Thomas Wilson; Mark Stringer (Geotechnical and Geological Engineering, 2024)
The North Island of New Zealand is a region of high volcanic activity, with significant eruptions over the past. Analogous to past events, future volcanic eruptions would produce a considerable volume of ash and granular soils, covering widespread areas and raising concerns for their disposal and storage. Such deposits, primarily airfall tephra, could be potentially used in geotechnical engineering applications such as foundations, roadway embankments and land reclamations. However, before their use as structural fills can be recommended, detailed laboratory investigations of their physical, chemical, compaction, and geotechnical engineering properties (strength, compressibility, collapsibility, liquefaction potential, etc.) must be conducted. Different tephra deposits can be products of different eruptions, so chemical composition analyses can be combined with the physical, compaction, and engineering properties to characterize such deposits. Accordingly, this paper provides useful insights from physical (grain size, specific gravity, and morphology), chemical (elemental and mineralogy using X-ray fluorescence and X-ray diffraction), and compaction tests (maximum dry density, optimum water content, and particle breakage) for eleven selected volcanic tephra samples sourced from the North Island of New Zealand in the Rotorua, Taupo, and Auckland regions.

Wastewater treatment, energy consumption, and greenhouse gas emissions: An operational approach to comparing Barcelona and Mexico City - Monserrat Ramírez-Melgarejo; Thomas Stringer (Journal of Environmental Management, 2024)

Sustainability of White Oak ( Quercus alba ) Timber Supply in Kentucky - Gaurav Dhungel; Thomas O Ochuodho; John M Lhotka; Jeffrey W Stringer; Kamana Poudel (Journal of Forestry, 2024)
White oak is a major commercial tree species and an important timber resource in Kentucky. However, current forest inventory trends from the Central Hardwood Forest Region (CHFR) reveal a sustainability threat from declining white oak regeneration and recruitment leading to a disproportionate inventory structure. Using Forest Inventory and Analysis (FIA) data together with the Forest Vegetation Simulator (FVS), we performed a base run analysis of projected inventory levels of white oak sawlogs to better understand whether the inventory level is sustainable to support the current harvest level of white oak in the future. The projections were further examined by tree grades to provide a general outlook on the quality of white oak timber growing in Kentucky’s forests in posterity. By doing so, we generated results that indicate that projected inventory levels of white oak sawlogs cannot be considered sustainable to support current harvest levels from 2058 onwards. In addition, the long-term trends in inventory levels of high-quality white oak sawlogs would be continuously declining whereas that of low-quality sawlogs would be steadily increasing. On the brink of these significant inventory shifts, our study calls for proactive forest management approaches to stabilize the white oak timber resource supply in Kentucky and beyond.

Smallholder perceptions of land restoration activities: rewetting tropical peatland oil palm areas in Sumatra, Indonesia - Caroline Ward; Lindsay C. Stringer; Eleanor Warren-Thomas; Fahmuddin Agus; Merry Crowson; Keith Hamer; Bambang Hariyadi; Winda D. Kartika; Jennifer Lucey; Colin McClean; Neneng L. Nurida; Nathalie Petorelli; et al. (Regional Environmental Change, 2021)
The Indonesian government committed to restoring over 2 million ha of degraded peatland by the end of 2020, mainly to reduce peat fires and greenhouse gas emissions. Although it is unlikely the government will meet this target, restoration projects are still underway. One restoration strategy involves blocking peatland drainage canals, but the consequences of this for smallholder farmers whose livelihoods are dependent on agriculture are unclear. This paper investigates perceived impacts of canal blocks on smallholder farmers and identifies factors that affect their willingness to accept canal blocks on their land. We use data from 181 household questionnaires collected in 2018 across three villages in Jambi province, Sumatra. We found that the majority of respondents would accept canal blocks on their farms, perceiving that the blocks would have no impact on yields or farm access, and would decrease fire risk. Respondents who would not accept blocks on their farms were more likely to use canals to access their farms and perceive that canal blocks would decrease yields. The majority of farmers unwilling to accept canal blocks did not change their mind when provided with an option of a block that would allow boat travel. Our results improve understanding of why some smallholders may be unwilling to engage with peatland restoration. Further research is needed to understand the impact of canal blocks on smallholders’ yields. Engaging with stakeholders from the outset to understand farmers’ concerns, and perceptions is key if the government is to succeed in meeting its peatland restoration target and to ensure that the costs and benefits of restoration are evenly shared between local stakeholders and other actors.

Population history and genetic bottlenecks in translocated Cook Strait giant weta, Deinacrida rugosa: recommendations for future conservation management - Daniel J. White; Corinne Watts; Julia Allwood; Diana Prada; Ian Stringer; Danny Thornburrow; Thomas R. Buckley (Conservation Genetics, 2017)

The biodiversity of the United Kingdom’s Overseas Territories: a stock take of species occurrence and assessment of key knowledge gaps - Thomas Churchyard; M. A. Eaton; S. Havery; J. Hall; J. Millett; A. Farr; R. J. Cuthbert; C. Stringer; J. A. Vickery (Biodiversity and Conservation, 2016)

Empowering Forestry Extension with Geospatial Technology - Songlin Fei; William Thomas; Jeffrey Stringer (Journal of Forestry, 2009)
Although geospatial technology has become an essential tool in forestry, it has not been widely applied in forestry extension and continuing education. Geospatial technology can be used to enhance our understanding of extension audiences and improve our ability to strategically plan education and training programs. In this article, we used the University of Kentucky's Cooperative Extension forestry program as an example to illustrate how geospatial technology can assist program planning, monitor and predict trends, identify service gaps, improve information dissemination, and foresee extension opportunities.